Use of study design principles would increase the reproducibility of reviews in conservation biology. (January 2020) - Grames, Eliza M.; Elphick, Chris S.
Abstract: Despite the importance of reviews and syntheses in advancing our understanding of the natural world and informing conservation policy, they frequently are not conducted with the same careful methods as primary studies. This discrepancy can lead to controversy over review conclusions because the methods employed to gather evidence supporting the conclusions are not reproducible. To illustrate this problem, we assessed whether the methods of reviews involved in two recent controversies met the common scientific standard of being reported in sufficient detail to be repeated by an independent researcher. We found that none of the reviews were repeatable by this standard. Later stages of the review process, such as quantitative analyses, were generally described well, but the more fundamental, data-gathering stage was not fully described in any of the reviews. To address the irreproducibility of review conclusions, we believe that ecologists and conservation biologists should recognize that literature searches for reviews are a data gathering exercise and apply the same rigorous study design principles and reporting standards that they would use for primary studies. Highlights: Reviews can be controversial when the synthesis process is not transparent. Viewing literature searches as data-gathering may increase reproducibility. Recent case studies illustrate the problem, but we suspect they are not unusual. We should conduct reviews and report methods with the same rigor as primary studies.